Tackling gaps in developing life‐changing treatments for dementia. Issue 1 (25th June 2019) - Mauricio, Rui; Benn, Caroline; Davis, John; Dawson, Gerry; Dawson, Lee A.; Evans, Alison; Fox, Nick; Gallacher, John; Hutton, Mike; Isaac, John; Jones, Declan N.C.; Jones, Lesley; et al.
Abstract: Since the G8 dementia summit in 2013, a number of initiatives have been established with the aim of facilitating the discovery of a disease‐modifying treatment for dementia by 2025. This report is a summary of the findings and recommendations of a meeting titled "Tackling gaps in developing life‐changing treatments for dementia", hosted by Alzheimer's Research UK in May 2018. The aim of the meeting was to identify, review, and highlight the areas in dementia research that are not currently being addressed by existing initiatives. It reflects the views of leading experts in the field of neurodegeneration research challenged with developing a strategic action plan to address these gaps and make recommendations on how to achieve the G8 dementia summit goals. The plan calls for significant advances in (1) translating newly identified genetic risk factors into a better understanding of the impacted biological processes; (2) enhanced understanding of selective neuronal resilience to inform novel drug targets; (3) facilitating robust and reproducible drug‐target validation; (4) appropriate and evidence‐based selection of appropriate subjects for proof‐of‐concept clinical trials; (5) improving approaches to assess drug‐target engagement in humans; and (6) innovative approaches in conducting clinical trials if we are able to detect disease 10–15 years earlier than we currently do today.